Enhancing Cocoa Bean Quality through Optimized Roasting Techniques for Sustainable Local Chocolate Production - Yuhendra AP; Reza Kusuma Nurrohman; Mi’raj Fuadi; Rahmat Sabani; Joko Sumarsono; Guyup Mahardhian Dwi Putra; Diah Ajeng Setiawati; Surya Abdul Muttalib; Isnaini Puspitasari; Fakhrul Irfan Khalil; Endang Purnama Dewi; Wan Rosli Bin Wan Ishak; Haslina Ahmad (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This activity aims to improve the quality of cocoa beans and promote sustainable local chocolate production through the application of optimized roasting techniques tailored to the characteristics of locally grown tropical cocoa beans. The program was led by Prof. Wan Rosli Bin Wan Ishak from USM, accompanied by Prof. Haslina Ahmad, along with collaborators from the field of Bioactive Materials and Synthesis at UPM. The activities included the delivery of training modules entitled Enhancing Cocoa Bean Quality through Optimized Roasting Techniques for Sustainable Local Chocolate Production, demonstrations of roasting processes involving parameters such as temperature, roasting time, humidity, and variations in roasting schemes, as well as a field visit to the chocolate production house at Kampung Coklat Senare. This visit aimed to provide a deeper understanding of the production workflow, the diversity of local cocoa beans, and opportunities to strengthen supply chains based on locally sourced raw materials. The primary focus of the program was the design of energy-efficient roasting strategies with minimal environmental impact, while preserving bioactive compounds and characteristic cocoa aromas through controlled Maillard reaction pathways. The initiative emphasized technology transfer, community capacity building, and the adoption of sustainable production practices among cocoa-based micro, small, and medium enterprises (MSMEs) in North Lombok. The long-term impact is expected to be reflected in improved processing efficiency, greater utilization of local resources, and more stable income opportunities for cocoa farmers and local MSME actors. The activity was conducted at Kampung Coklat Senare, Genggelang Village, North Lombok, on 21 January 2026, highlighting the importance of international–local partnerships within the context of community engagement in tropical regions.